Experimental Study on Combustion Properties and Thermo-Gravimetric Analyses of Oriented Strand Board (OSB) - Yapici, F. (Journal Drvna Industrija beljo@sumfak.hr, 2020)
This study investigates the effects of types of adhesives on the combustion properties of oriented strand board panels (OSB). Combustion test was performed according to ASTM E69 standard. Mass reduction, change of temperature and released gas (CO, NO, O2 ) were measured every 30 seconds during this test. Thermogravimetric analysis (TGA) of the OSBs was also carried out. While the highest temperature value of combustion was only obtained for the samples with phenol-formaldehyde at both outer and inner layer of test panels, the lowest temperature value was obtained for test samples with phenol-formaldehyde on the outer layer and isocyanate on the atinner layer. In the results of TGA, test mass reduction of OSBs was similar to each other, and most of the mass loss occurred at the temperatures between 200 and 400 °C. © 2020 by the author(s).
Eksperimentalna Istraživanja Svojstava Gorenja ve Termogravimetrijska Analiza Ploča Iverica S Usmjerenim Makroiverjem (OSB)
Keywords: Combustion; Oriented Strand Board; Phenol-Formaldehyde; Thermo-Gravimetric Analysis